2019
DOI: 10.1177/1099800419880615
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Prepregnancy Obesity and Excessive Gestational Weight Gain on Maternal and Child Gastrointestinal Microbiome Composition: A Systematic Review

Abstract: Background: Maternal obesity is a well-known risk factor for significant obstetric and neonatal complications. The influence of the gastrointestinal microbiome in the setting of maternal obesity during pregnancy is less understood. The purpose of this systematic review is to synthesize the literature on the relationships between maternal obesity and excessive gestational weight gain (EGWG) and the composition of maternal and child gastrointestinal microbiomes. Method: We searched CINHAL, OVID Medline, Web of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 61 publications
(121 reference statements)
2
27
0
1
Order By: Relevance
“…Such differences were reported in pregnant women (Collado et al, 2008;Dreisbach et al, 2020) regarding not only intestinal microbiota but also the microbiota associated with breast milk (Cabrera-Rubio et al, 2012;Lundgren et al, 2019), and vaginal mucosa (Si et al, 2017). Despite some discrepancies (e.g., Stanislawski et al, 2017), differences were also found among descendants depending on whether they were born to obese or lean mothers (for review, see Dreisbach et al, 2020). Such a finding is consistent with the major contribution of maternal microbiotas to the initial colonization of the infant's gastrointestinal tract (Ferretti et al, 2018).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Such differences were reported in pregnant women (Collado et al, 2008;Dreisbach et al, 2020) regarding not only intestinal microbiota but also the microbiota associated with breast milk (Cabrera-Rubio et al, 2012;Lundgren et al, 2019), and vaginal mucosa (Si et al, 2017). Despite some discrepancies (e.g., Stanislawski et al, 2017), differences were also found among descendants depending on whether they were born to obese or lean mothers (for review, see Dreisbach et al, 2020). Such a finding is consistent with the major contribution of maternal microbiotas to the initial colonization of the infant's gastrointestinal tract (Ferretti et al, 2018).…”
Section: Introductionsupporting
confidence: 54%
“…Most studies comparing the fecal microbiotas of obese or overweight subjects with lean ones concluded that there were differences in composition (for review, see Gerard, 2016). Such differences were reported in pregnant women (Collado et al, 2008;Dreisbach et al, 2020) regarding not only intestinal microbiota but also the microbiota associated with breast milk (Cabrera-Rubio et al, 2012;Lundgren et al, 2019), and vaginal mucosa (Si et al, 2017). Despite some discrepancies (e.g., Stanislawski et al, 2017), differences were also found among descendants depending on whether they were born to obese or lean mothers (for review, see Dreisbach et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A recent in vivo study employing germ-free (GF) mice colonized with stool microbes from 2-week-old infants born from obese or normal-weight mothers demonstrated the causative role of maternal obesity-associated infant dysbiosis in childhood obesity and NAFLD [111]. High maternal pre-gestational body mass index (BMI) is associated with an altered infant microbiome from the first days of life until 2 years of age, bifidobacteria being one of the genera most affected, and can also shape the composition and diversity of the breast milk microbiota [61,112,113]. Recent evidence has shown that pre-gestational normal-weight women with exclusive breastfeeding habits harbored a significantly higher abundance of the Bifidobacterium genus in the breast milk that could also have an impact on infant development and health [61].…”
Section: Bifidobacterium Genus As a Biomarker Of Metabolic Diseases In Infanthoodmentioning
confidence: 99%
“…The maternal microbiota is considered to be the main driver of the initial bacterial seeding of the newborn [11]; however, the perinatal factors that affect the maternal microbiota are little understood, as prior studies have tended to focus on the factors shaping the infant microbiome [12,13]. Only a few studies have investigated the maternal microbiota and the elements that could modify its composition, including the mother's diet during gestation [14][15][16][17][18], pregestational body mass index (BMI) [19,20], or weight gained during gestation [21]. In these studies, the importance of these factors, especially the maternal diet (e.g., fiber and fat-related nutrients), on intestinal microbiota at delivery was highlighted.…”
Section: Introductionmentioning
confidence: 99%